Menggagas peran diseminasi pengetahuan pada layanan penelusuran informasi “Sapa Pustakawan” di Perpustakaan IAIN Kudus - Radiya Wira Buwana (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The research in this paper aims to find out how the form of the role of knowledge dissemination can be carried out by the information retrieval Sapa Pustakawan service to the users at the IAIN Kudus Library. This research was conducted with a descriptive research approach . The data collection method used in this study is through the observation method and is supported by data collection through the library research method. Data analysis was carried out by comparing the findings of observations in the field with the theories obtained in the library research method, then synthesis was carried out to find a concept. The results of this study indicate that the form of the role of knowledge dissemination that can be carried out by the Sapa Pustakawan service at the IAIN Kudus Library is 1.) being able to provide knowledge to users to have the ability to search for correct information in print and digitally/online. 2.) able to provide knowledge to users about how to utilize and use reference manager tools applications such as Zotero or Mendeley applications. 3) able to provide knowledge to users to have the ability to avoid plagiarism of scientific work. In this study, it was also known that due to the uncontrolled covid-19 pandemic, the IAIN Kudus Library took a policy to further simplify the role of the Sapa Pustakawan service. The Sapa Pustakawan service only serves the search for sources of information needed by users through a telegram social media group.